Analysis of Energy Management System and Feasibility of 25 kWp Rooftop Solar Power Plant using Techno-Economic Method in DKI Jakarta Regional Government Building - Septian, Angga; Irianto, Chairul G.; Sari, Lydia (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2026)
The building sector is a major contributor to energy consumption and greenhouse gas emissions in Indonesia, accounting for approximately 50% of national energy use and nearly 30% of total emissions. This study evaluates the implementation of an ISO 50001–based Energy Management Systems (EnMS) in a government building in Jakarta, combining energy efficiency retrofits with rooftop photovoltaic (PV) integration. The research contributes a comprehensive technical and economic assessment that quantifies energy savings, emission reductions, and financial feasibility within a replicable public-sector framework. The methodology included an ISO 50001–aligned energy audit, building energy simulation using DesignBuilder, PV system design with PVsyst, and economic feasibility analysis. LED lighting retrofits reduced lighting energy consumption by 38.14%, while air-conditioning optimization improved thermal comfort. A 24.75 kWp rooftop PV system generated 33,428 kWh annually, supplying 17.97% of the building’s electricity demand. In total, the integrated measures achieved annual energy savings of 37,587 kWh and reduced emissions by 31.57 tons of CO₂. Economic analysis indicated that the project was financially feasible, with a positive NPV, a 6% IRR, an 8.18% ROI, and a payback period of approximately 14 years. The integrated approach proved effective and showed strong potential for replication in similar public buildings.